Differentiated Instruction in Teaching from the International Perspective Methodological and empirical insights - Maulana, Ridwan; Helms-Lorenz, Michelle; Moorer, Peter; Smale-Jacobse, Annemieke; Feng, Xiangyuan (University of Groningen Press, 2023)
This book reports findings based on a largescale project on differentiated instruction across various education systems documenting evidence of its measurement, differences, changes, and links with student engagement. We document empirical findings of differentiated instruction practices in secondary education across diverse countries/education systems, covering student, teacher, school, and education system/country levels. Classroom observations and student surveys, both collected in authentic classrooms, are the core measures of inquiry used. Findings on similarities and differences in differentiated instruction practices, changes over time, links with student engagement, and the role of some personal and contextual factors, contribute to advance the knowledge base particularly in the field of teaching effectiveness, learning environments research, and differentiation in education. Findings are relevant for research, practice, and policy.